Nursing cooperation in root canal retreatment of infected root canals (护理配合在感染根管再治疗中的应用效果) - LI Yuling (李玉玲); LUAN Xiaoyu (栾晓宇); ZHANG Weihong (张卫红); WANG Qian (王倩) (中西医结合护理)
Objective To evaluate the nursing cooperation in root canal retreatment of infected root canal. Methods Totally 60 patients with infected root canals of molar teeth requiring root canal retreatment were randomly divided into the control group and observation group, with 30 cases in each group. All patients received routine nursing during the treatment, and those in the observation group were given refined nursing management. The operation time was recorded and compared between two groups. Results The operation time of the observation group was significant shorter than that of control group, with a significant difference(P＜0. 05). Conclusion A comprehensive and refined management of nursing cooperation may help shorten the operation time of root canal retreatment, reduce the risk of infection, relieve of fatigue of both dentists and patients, and improve the comfort of patient during the treatment. (目的 探讨护理配合在感染根管再治疗中的应用效果。方法 选取2019年1月—2020年1月收治的60例需要进行根管再治疗的后牙感染根管患者作为研究对象, 采用数字随机表法分为对照组和观察组, 各30例。对照组给予常规护理, 观察组在对照组基础上细化护理配合。观察两组磨牙感染根管进行再治疗的操作时间。结果 观察组磨牙感染根管进行再治疗的操作时间低于对照组, 差异有统计学意义(P＜0. 05)。结论 患者在进行感染根管再治疗时, 给予全面的护理配合, 有助于缩短再治疗操作时间, 对降低感染风险、缓解治疗中医患双方疲劳和提高患者舒适度具有积极意义。)